2017
DOI: 10.3390/ijms18102198
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Matricellular Proteins in Oncogenic Virus-Induced Cancers and Their Potential Utilities as Therapeutic Targets

Abstract: Matricellular proteins differ from other classical extracellular matrix proteins; for instance, they are transiently expressed as soluble proteins rather than being constitutively expressed in pathological conditions, such as acute viral infections. Accumulating studies have revealed that matricellular proteins, including osteopontin and tenascin-C, both of which interact with integrin heterodimers, are involved in inflammatory diseases, autoimmune disorders, and cancers. The concentrations of these matricellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 119 publications
(131 reference statements)
0
17
0
Order By: Relevance
“…The difference in localization of positive-staining products is interesting, as seen by intracellular staining by 34E3, and extracellular staining by 10A16. Different interacting molecules of the N-half of OPN (integrin) and the C-half of OPN (CD44 variant) may explain these results [ 28 ]. The C-half of OPN may interact with CD44, and this interaction may facilitate the release of the molecule, since it is reported that soluble plasma CD44 levels are closely associated with OPN in adult T-cell lymphoma (ATL) and MTB infection [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in localization of positive-staining products is interesting, as seen by intracellular staining by 34E3, and extracellular staining by 10A16. Different interacting molecules of the N-half of OPN (integrin) and the C-half of OPN (CD44 variant) may explain these results [ 28 ]. The C-half of OPN may interact with CD44, and this interaction may facilitate the release of the molecule, since it is reported that soluble plasma CD44 levels are closely associated with OPN in adult T-cell lymphoma (ATL) and MTB infection [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…OPN interacts with ECM elements like collagen and fibronectin, as well as with calcium due to its Ca 2+ binding sequence [60]. For cell adhesion, OPN possesses integrin-binding sites—an RGD sequence in position 159–161 recognized by integrins αvβ1, αvβ3, αvβ5, α5β1, and α8β1, and the SVVYGLR motif (amino acids 162–168) bound by integrins α9β1, α4β1, and α4β7 [8]. Moreover, the C-terminus of OPN is recognized by the CD44 splice variants CD44v3, CD44v6, and CD44v7 [8].…”
Section: Reviewmentioning
confidence: 99%
“…For cell adhesion, OPN possesses integrin-binding sites—an RGD sequence in position 159–161 recognized by integrins αvβ1, αvβ3, αvβ5, α5β1, and α8β1, and the SVVYGLR motif (amino acids 162–168) bound by integrins α9β1, α4β1, and α4β7 [8]. Moreover, the C-terminus of OPN is recognized by the CD44 splice variants CD44v3, CD44v6, and CD44v7 [8]. OPN cleavage by matrix metalloprotease 3 (MMP3), MMP7, and thrombin renders the above motifs more accessible and enhances binding efficiency [4,61].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed the critical role of T cell immunity in the control of tuberculous infection, and defects in T cytokine production, particularly interferon-γ (IFN-γ), are genetically responsible for the development of human tuberculosis disease [ 30 ]. Osteopontin (OPN) is a highly negatively charged, arginine-glycine-aspartate (RGD)-containing and O-glycosylated phosphoprotein with little or no detectable tertiary structure by nuclear magnetic resonance (NMR) spectroscopy, encoded by a single gene clustered on chromosome 4 in human beings and produced by several types of cells such as osteoclasts, endothelial cells, epithelial cells and immune cells [ 31 , 32 ]. It contains several cell interacting domains, with accumulating evidence revealing its stimulation to signal transduction pathways via RGD-dependent (α V β 1 , α V β 3 or α V β 5 ) and RGD-independent (α 4 β 1 , α 5 β 1 , α 8 β 1 or α 9 β 1 ) integrins and CD44 variants at the cell surface, mediating cell adhesion, migration and survival in a variety of inflammatory cells including T cells, macrophages and NK cells [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%